La aplicación de los juegos didácticos como estrategia metodológica para fortalecer el desarrollo lógico matemático en niñas y niños del nivel inicial del centro educativo comunitario intercultural bilingüe Monseñor Leónidas Proaño Nº2 de la comunidad Lancapac, parroquia San Lucas, cantón y provincia de Loja período 2014-2015 - Tene Quizhpe, Yaguarcisa (2016)
The investigation has been titled: The application of the didactic games as methodological strategy to strengthen the logical mathematical development in girls and children of the initial level of the educational community center Intercultural Bilingual Monseñor Leonidas Proaño N°2 of the community Lancapac, San Lucas, canton and province of Loja period 2014-2015, as general objective thought about: To apply the didactic games as methodological strategy to strengthen the logical mathematical development in the children and girls of the initial level of the educational community center Intercultural Bilingual Monseñor Leonidas Proaño N°2 of the community of Lancapc, San Lucas, canton and province of Loja, period 2014 -2015. The present investigation It was a study of type descriptive and correlacional, one worked with the following methods: The descriptive, inductive-deductive, analytic, synthetic, as technical and instruments were applied the survey directed to the master level, the test and the re-test applied to the children of initial level, the application of the strategy he/she went in agreement to the planning of the activities with the purpose of reinforcing the area of difficulty, because at first it was found great difficulty of mathematical development at this age once finished the application test, re-test in positive results within each area measuring test were obtained that respondents to the general outlined objective, one worked with a total population of 13 girls and children. He concluded stating that the didactic games established important changes inside the logical mathematical knowledge in the girls and children of the initial level of the educational center Monseñor Leonidas Proaño N°2.